2019
DOI: 10.3390/ijerph16020175
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Vitamin D3 and Metabolic Syndrome

Abstract: The growing number of overweight and obese individuals is an alarming global problem; these conditions are risk factors for the development of health problems such as metabolic syndrome (MetS), type-2 diabetes, atherosclerosis, and cardiovascular disease. Numerous studies have suggested that vitamin D3 deficiency plays a role in the pathogenesis of MetS. The aim of this study was to analyze the relationship between MetS and vitamin D3 levels in women. Laboratory analysis demonstrated that only 26.89% of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
2
16
1
Order By: Relevance
“…Interestingly, our study demonstrated that Vitamin D 3 deficiency <20ng/ml and BMI >35 were significant predictors for metabolic syndrome. This in agreement with a study of Wang and his colleagues that concluded that low Vitamin D 3 concentration is an independent risk factor for M.S [17,18].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our study demonstrated that Vitamin D 3 deficiency <20ng/ml and BMI >35 were significant predictors for metabolic syndrome. This in agreement with a study of Wang and his colleagues that concluded that low Vitamin D 3 concentration is an independent risk factor for M.S [17,18].…”
Section: Discussionsupporting
confidence: 93%
“…We did not find association of vitamin D with MS. This is similar to the observation of Kwon and Lim in Korean population and Wieder-Huszla et al 2019 in women of Poland 12,14 . Vitamin D was not found as an independent predictor of fasting lipids in a British Bangladeshi adults 15 .…”
Section: Discussionsupporting
confidence: 92%
“…The binding of the active metabolite of vitD (1,25(OH) 2 D 3 or calcitriol) with its nuclear receptor, the VDR, which forms a heterodimeric complex with the retinoic acid receptor and interacts with transcript factors, results in the regulation of hundreds of different genes [ 32 , 33 ], increasing the intestinal and kidney absorption of calcium. A deficiency in vitD results in secondary hyperparathyroidism, causing increased osteoclast activity, osteopenia, and osteoporosis [ 34 ].…”
Section: Vitamin D and The Immune Systemmentioning
confidence: 99%